Hubungan Komunikasi Terapeutik Perawat Terhadap Kepuasan Pasien Pada Pelayanan Kesehatan - Nurwahyuni, Fadilah Siti; Sutresna, Iyos; Dolifah, Dewi (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
In nursing, therapeutic communication is a very important component for establishing professional relationships with patients. A nurse who has the ability to communicate therapeutically with patients will find it easy to establish a relationship of mutual trust with the patient. The level of success of a health service can be assessed from the communication provided by the nurse to the patient. When nurses carry out therapeutic communication with patients, patients will feel satisfaction with the services provided. The aim of this research is to determine and analyze the relationship between nurses' therapeutic communication and patient satisfaction with health services at the UPTD of the Tanjungsari health center, Sumedang district. This research was conducted by taking 52 respondents from outpatients of the UPTD Tanjungsari Health Center, Sumedang Regency. This type of research uses quantitative methods with a cross sectional approach and the sampling technique used is accidental sampling. The results of this research showed that there was a relationship between nurses' therapeutic communication and patient satisfaction with health services at the Tanjungsari Health Center, Sumedang Regency with the result p = 0.001 < 0.05. From this research it can be concluded that therapeutic communication carried out by nurses has a very positive impact on patient satisfaction with health services.